Prospects for the use of wind energy resources at the Akademik Vernadsky station - K. Petrenko; I. Ivanchenko; O. Karmazin (Ukrainian Antarctic Journal, 2021)
Renewable energy and other methods of minimizing emissions into the atmosphere should be a priority for each country. This approach should be extended to Antarctica scientific stations. The study main objective was to obtain the necessary estimates of the wind energy potential of the Galindez Island territory to estimate the feasibility of installing wind turbines on the territory of the Akademik Vernadsky station. The study of the wind properties over the territory was based on the British Antarctic Survey archive of meteorological parameter average annual values (1950–2020), 3-h wind speed and direction data, registered by the Akademik Vernadsky station (2011–2020), and average daily data from meteorological observations (2014–2018). The Hellman parameter was calculated from satellite data. A number of statistical methods were used to analyze the vertical wind profile, particularly the method of minimizing the arithmetic mean relative modeling error. To assess the amount of generation, the wind speed data at the height of the anemometer sensor were recalculated to the height of the wind turbine axis. Using the wind power characteristics provided by the developers, average annual wind power generation was avaluated. For calculations of wind energy potential, we chose the technique developed by the Department of Wind Power of the Institute of Renewable Energy of the National Academy of Sciences of Ukraine. The analysis of the wind conditions showed a high average daily wind speed (3.9 m/s) and the prevailing wind direction (NNE 24%). The results support the hypothesis about the expediency of installing wind turbines on the territory of the Akademik Vernadsky station. The wind turbine was selected for further wind power calculations based on the other countries experience of using wind turbines in Antarctica and considering the specifics of installation and operation in conditions of high wind speeds, low temperatures and high relative humidity. Based on information on fuel consumption at the Akademik Vernadsky station, it was estimated that the installation of 10 wind turbines SD6 would meet 28.4% of the station's yearly electricity needs.